Cathepsin L promotes chemresistance to neuroblastoma by modulating serglycin - Du, Xiaohuan; Ding, Leyun; Huang, Shungen; Li, Fang; Yan, Yinghui; Tang, Ruze; Ding, Xinyuan; Zhu, Zengyan; Wang, Wenjuan (Frontiers in Pharmacology, 2022)
Cathepsin L (CTSL), a lysosomal acid cysteine protease, is found to play a critical role in chemosencitivity and tumor progression. However, the potential roles and molecular mechanisms of CTSL in chemoresistance in NB are still unclear. In this study, the correlation between clinical characteristics, survival and CTSL expression were assessed in two independent patient datasets. The chemoresistant to cisplatin or doxorubicin was detected using CCK-8 assay. Western blot was employed to detect the expression of CTSL, multi-drug resistance proteins, autophagy-related proteins and apoptosis-related proteins in NB cells while knocking down CTSL. Lysosome staining was analyzed to access the expression levels of lysosomes in NB cells. The expression of apoptosis markers was analyzed with immunofluorescence. Various datasets were analyzed to find the potential protein related to CTSL. In addition, a subcutaneous tumor xenografts model in M-NSG mice was used to assess tumor response to CTSL inhibition in vivo. Based on the validation dataset (Versteeg), we confirmed that CTSL served as a prognostic marker for poor clinical outcome in NB patients. We further found that the expression level of CTSL was higher in SK-N-BE (2) cells than in IMR-32 cells. Knocking down CTSL reversed the chemoresistance in SK-N-BE (2) cells. Furthermore, combination of CTSL inhibition and chemotherapy potently blocked tumor growth in vivo. Mechanistically, CTSL promoted chemoresistance in NB cells by up-regulating multi-drug resistance protein ABCB1 and ABCG2, inhibiting the autophagy level and cell apoptpsis. Furthermore, we observed six datasets and found that Serglycin (SRGN) expression was positively associated with CTSL expresssion. CTSL could mediate chemoresistance by up-regulating SRGN expression in NB cells and SRGN expression was positively correlated with poor prognosis of NB patients. Taken together, our findings indicate that the CTSL promotes chemoresistance to cisplatin and doxorubicin by up-regulating the expression of multi-drug resistance proteins and inhibiting the autophagy level and cell apoptosis in NB cells. Thus, CTSL may be a therapeutic target for overcoming chemoresistant to cisplatin and doxorubicin in NB patients.